ANALISIS KOMPARATIF USAHA TANI PADI ORGANIK DENGAN PADI NON ORGANIK (Studi Kasus : Desa Lubuk Bayas Kecamatan Perbaungan Kabupaten Serdang Bedagai) - Febri Giola Pinem; Juliana Br Simbolon; Fandri Siburian; Roida Ervina Sinaga (Universitas Quality, 2020)
The aim of study is to analyze the factors that affect the production of organic rice farm and non-organic rice farm businesses, comparison of organic rice farm and non-organic rice farm businesses and analyze appropriateness of organic rice farm and non-organic rice farm businesses in researh area. The method of study that used was multiple linear regression analysis, method of cultivation analysis and feasibility analysis. The data used is primary and secondary. The result of study concluded on the independent variabel analysis of organic rice farm and non-organic rice farm businesses, the most dominant in influencing the output on organic rice which are pesticides and fertilizer. Meanwhile, the rice farm is non organic, the most dominant in influencing the output on non organic rice which are seeds and breadth of land. Organic rice farm incomes in Lubuk Bayas village Perbaungan sub district Serdang Bedagai regency is Rp 25.753.659,/ha and the income of non organic farm business is Rp 20.503.554,-/ha. Non organic rice farm business has R/C value higher than organic rice.